INTERNATIONAL COLLABORATION BETWEEN POST-GRADUATE PROGRAMS STRICTU SENSU - Elizabeth Bernardino; Clemence Dallaire; Maria Ribeiro Lacerda (Universidade Federal do Paraná, 2011)
This work intends to relate the experience of collaboration - starting toward the end of 2008 - between professors of the Nursing post-graduate programs stricto sensu of the Federal University of Parana and Laval University in Canada. Strategies include the participation in examining panels for proposal defense, opportunities to present at, and participate in, international congresses financed by the Coordination for the Perfection of Higher Education Personnel, the Araucaria Foundation, and the Federal University of Parana, co-orientation of students and the offering of distance learning courses. Technical and facilitating elements permitted those involved to overcome geographical distances and cultural differences and take the partnership forward. The challenges are numerous and have to do with the bearing of the cost of integrative actions, sufficient fluency in the foreign language, and difficulty in conciliating approaches and research topics. The benefits are related to the discussion and analysis of professional practice in Nursing under new approaches in different contexts.